Danish system of labour relations; Study in industrial peace - Galenson, Walter (Massachusetts, 1952)
The first volume of Economic and Industrial Life and Relations describes the goal and the pathway to non-vio lent Socialism of Gandhiji's conception. The second volume is devoted to the economic teachings of Gandhiji. In the third volume his ideas and views on agrarian and indus trial conditions and relations are set out. In these writings will be found the principles he enunciates and how they could be translated into practice and applied to the pro blems confronting us. In short, he shows the ways and means to reduce the ideal to the terms of the actual.
Keywords: Industrial relations - Danish